Determinants of fruit and vegetable intake among 11-year-old schoolchildren in a country of traditionally low fruit and vegetable consumption - Due Pernille; De Bourdeaudhuij Ilse; Thorsdottir Inga; Kristjansdottir Asa G; Wind Marianne; Klepp Knut-Inge (BMC, 2006)
Abstract Background Fruit and vegetable consumption is traditionally low in Iceland. The results of the Pro Children cross-Europe survey showed that the consumption was lowest among children in Iceland. The aim of this study was to identify determinants of fruit and vegetable intake among 11-year-old schoolchildren in Iceland. Methods A cross-sectional survey was performed in Iceland in the autumn of 2003 as a part of the Pro Children cross-Europe survey. The survey was designed to provide information on actual consumption levels of vegetables and fruits by 11-year-old school children and to assess potential determinants of consumption patterns. A total of 1235 Icelandic children (89%) from 32 randomly chosen schools participated. Hierarchical regression analyses were performed to determine the explained variance of the children's fruit and vegetable intake. In these analyses socio-demographic background variables were entered as a first block, perceived physical-environmental variables as a second block, perceived socio-environmental variables as a third block and personal variables as a fourth block. Results 64% of the children ate fruit less than once a day, and 61% ate vegetables less than once a day. Respectively, 31% and 39% of the variance in children's fruit and vegetable intake was explained by the determinants studied. About 7% and 13% of the variance in fruit and vegetable intake was explained by the perceived physical-environmental determinants, mainly by availability at home. About 18% and 16% of the variance in fruit and vegetable intake was explained by the personal determinants. For both fruit and vegetable intake, the significant personal determinants were preferences, liking, knowledge of recommendations and self-efficacy. Conclusion Interventions to increase fruit and vegetable intake among children should aim at both environmental factors such as greater availability of fruit and vegetables, and personal factors as self-efficacy and knowledge levels concerning nutrition.